(untitled) (LEARNing Landscapes, 2012)
This article shares one junior faculty member’s account of how she and her students debated, deliberated about, decided to, and ultimately reshaped a traditional, foundational Principles of Education course in an undergraduate teacher education program. Three former childhood, art, and theater education students highlight their experiences, observing connections between their own and their instructor’s creativity and evolving philosophies of education. Together, they illustrate issues they confronted while reflecting individually and collectively on how and whether to creatively teach and learn, while also being constrained by practical, systemic realities.